(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2024)
This article analyzes the guidelines of the Municipal Education Network of Goiânia regarding the school inclusion of migrant children. The analysis is based on the four principles of the right to education established by the Committee on Economic, Social, and Cultural Rights, an entity linked to the United Nations. Based on that, the study was developed from the 2023 document “Linhas Guias – Orientações para recepção e acolhimento às crianças/estudantes imigrantes na RME de Goiânia” [Guiding Lines – Guidelines for the reception and welcoming of migrant children/students in the Municipal Education Network of Goiânia]. Content analysis was applied in data processing, with Atlas T.I. software used as an auxiliary tool. The results indicate: (1) the inclusion of children is not addressed in the document through a single approach but through three interconnected perspectives: education policy perspective, pedagogical perspective, and welcoming perspective; (2) cultural, social, and linguistic differences must be considered in the inclusion process. It is concluded that the document encompasses additional dimensions beyond enrollment that impact the permanence and success of children in school. However, empirical studies are required to assess the effectiveness of these guidelines in institutions. Keywords: Education policy. International migrations. Inclusion. Right to education.